Hyperthyroidism presenting as ST Elevation Myocardial Infarction with Normal Coronaries – A Case Report - Krishnan, Gayathri Devi (J ASEAN Fed Endocr Soc, 2019)
A 31-year-old male, apparently well, presented with typical chest pain. His ECG showed ST-elevation from V1-V4 and echocardiogram revealed anteroseptal wall hypokinesia with ejection fraction of 45%. Normal coronary arteries were seen on coronary angiogram. A thyroid function test showed elevated free T4 levels with suppressed thyroid stimulating hormone (TSH). Treatment with thionamides and beta-blockers improved symptoms. Upon review 4 months later he was well. Repeat echocardiogram showed good ejection fraction with no hypokinetic area.